Lead-free hybrid perovskites for photovoltaics - Stroyuk, Oleksandr (Beilstein Journal of Nanotechnology, 2018)
This review covers the state-of-the-art in organo–inorganic lead-free hybrid perovskites (HPs) and applications of these exciting materials as light harvesters in photovoltaic systems. Special emphasis is placed on the influence of the spatial organization of HP materials both on the micro- and nanometer scale on the performance and stability of perovskite-based solar light converters. This review also discusses HP materials produced by isovalent lead(II) substitution with Sn2+ and other metal(II) ions, perovskite materials formed on the basis of M3+ cations (Sb3+, Bi3+) as well as on combinations of M+/M3+ ions aliovalent to 2Pb2+ (Ag+/Bi3+, Ag+/Sb3+, etc.). The survey is concluded with an outlook highlighting the most promising strategies for future progress of photovoltaic systems based on lead-free perovskite compounds.
Keywords: light harvesting; low-toxic materials; organo-inorganic perovskites; solar cells

(untitled) - Green, M. A.; Hishikawa, Y.; Warta, W.; Dunlop, E. D.; Levi, D. H.; Hohl-Ebinger, J.; Ho-Baillie, A. W. H. (Prog. Photovoltaics, 2017)

(untitled) - Hagfeldt, A.; Boschloo, G.; Sun, L.; Kloo, L.; Pettersson, H. (Chem. Rev., 2010)

(untitled) - Sandroni, M.; Wegner, K. D.; Aldakov, D.; Reiss, P. (ACS Energy Lett., 2017)

(untitled) - Reiss, P.; Carrière, M.; Lincheneau, C.; Vaure, L.; Tamang, S. (Chem. Rev., 2016)

(untitled) - Wang, W.; Feng, W.; Du, J.; Xue, W.; Zhang, L.; Zhao, L.; Li, Y.; Zhong, X. (Adv. Mater., 2018)

(untitled) - Kazim, S.; Nazeeruddin, M. K.; Grätzel, M.; Ahmad, S. (Angew. Chem., Int. Ed., 2014)

(untitled) - Wang, B.; Xiao, X.; Chen, T. (Nanoscale, 2014)

(untitled) - Gamliel, S.; Etgar, L. (RSC Adv., 2014)

(untitled) - Giorgi, G.; Yamashita, K. (J. Mater. Chem. A, 2015)

(untitled) - Jung, H. S.; Park, N.-G. (Small, 2015)

(untitled) - Liu, X.; Zhao, W.; Cui, H.; Xie, Y.; Wang, Y.; Xu, T.; Huang, F. (Inorg. Chem. Front., 2015)

(untitled) - Luo, S.; Daoud, W. A. (J. Mater. Chem. A, 2015)

(untitled) - Zuo, C.; Bolink, H. J.; Han, H.; Huang, J.; Cahen, D.; Ding, L. (Adv. Sci., 2016)

(untitled) - Pedesseau, L.; Sapori, D.; Traore, B.; Robles, R.; Fang, H.-H.; Loi, M. A.; Tsai, H.; Nie, W.; Blancon, J.-C.; Neukirch, A.; Tretiak, S.; Mohite, A. D.; et al. (ACS Nano, 2016)

(untitled) - bin Mohd Yusoff, A. R.; Nazeeruddin, M. K. (J. Phys. Chem. Lett., 2016)

(untitled) - Saparov, B.; Mitzi, D. B. (Chem. Rev., 2016)

(untitled) - Polman, A.; Knight, M.; Garnett, E. C.; Ehrler, B.; Sinke, W. C. (Science, 2016)

(untitled) - Correa-Baena, J.-P.; Abate, A.; Saliba, M.; Tress, W.; Jesper Jacobsson, T.; Grätzel, M.; Hagfeldt, A. (Energy Environ. Sci., 2017)

(untitled) - Bhatt, M. D.; Lee, J. S. (New J. Chem., 2017)

(untitled) - Niu, G.; Guo, X.; Wang, L. (J. Mater. Chem. A, 2015)

(untitled) - Ono, L. K.; Juarez-Perez, E. J.; Qi, Y. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Calvo, M. E. (J. Mater. Chem. A, 2017)

(untitled) - Yang, S.; Fu, W.; Zhang, Z.; Chen, H.; Li, C.-Z. (J. Mater. Chem. A, 2017)

(untitled) - Dou, L. (J. Mater. Chem. C, 2017)

(untitled) - Matthews, P. D.; Lewis, D. J.; O'Brien, P. (J. Mater. Chem. A, 2017)

(untitled) - Assadi, M. K.; Bakhoda, S.; Saidur, R.; Hanaei, H. (Renewable Sustainable Energy Rev., 2018)

(untitled) - Dubey, A.; Adhikari, N.; Mabrouk, S.; Wu, F.; Chen, K.; Yang, S.; Qiao, Q. (J. Mater. Chem. A, 2018)

(untitled) - Kostopoulou, A.; Kymakis, E.; Stratakis, E. (J. Mater. Chem. A, 2018)

(untitled) - Ansari, M. I. H.; Qurashi, A.; Nazeeruddin, M. K. (J. Photochem. Photobiol., C, 2018)

(untitled) - Nakazaki, J.; Segawa, H. (J. Photochem. Photobiol., C, 2018)

(untitled) - Kim, B. J.; Lee, S.; Jung, H. S. (J. Mater. Chem. A, 2018)

(untitled) - Sum, T. C.; Mathews, N. (Energy Environ. Sci., 2014)

(untitled) - Hsiao, Y.-C.; Wu, T.; Li, M.; Liu, Q.; Qin, W.; Hu, B. (J. Mater. Chem. A, 2015)

(untitled) - Shi, J.; Xu, X.; Li, D.; Meng, Q. (Small, 2015)

(untitled) - Zhao, Y.; Zhu, K. (Chem. Soc. Rev., 2016)

(untitled) - Berhe, T. A.; Su, W.-N.; Chen, C.-H.; Pan, C.-J.; Cheng, J.-H.; Chen, H.-M.; Tsai, M.-C.; Chen, L.-Y.; Dubale, A. A.; Hwang, B.-J. (Energy Environ. Sci., 2016)

(untitled) - Saba, M.; Quochi, F.; Mura, A.; Bongiovanni, G. (Acc. Chem. Res., 2016)

(untitled) - Johnston, M. B.; Herz, L. M. (Acc. Chem. Res., 2016)

(untitled) - Mehmood, U.; Al-Ahmed, A.; Afzaal, M.; Al-Sulaiman, F. A.; Daud, M. (Renewable Sustainable Energy Rev., 2017)

(untitled) - Kadro, J. M.; Hagfeldt, A. (Joule, 2017)

(untitled) - Peng, J.; Chen, Y.; Zheng, K.; Pullerits, T.; Liang, Z. (Chem. Soc. Rev., 2017)

(untitled) - Abate, A. (Joule, 2017)

(untitled) - Ahmadi, M.; Wu, T.; Hu, B. (Adv. Mater., 2017)

(untitled) - Chakraborty, S.; Xie, W.; Mathews, N.; Sherburne, M.; Ahuja, R.; Asta, M.; Mhaisalkar, S. G. (ACS Energy Lett., 2017)

(untitled) - Green, M. A.; Ho-Baillie, A. (ACS Energy Lett., 2017)

(untitled) - Ono, L. K.; Qi, Y. (J. Phys. D: Appl. Phys., 2018)

(untitled) - Chen, P.; Bai, Y.; Lyu, M.; Yun, J.-H.; Hao, M.; Wang, L. (Sol. RRL, 2018)

(untitled) - Saliba, M.; Correa-Baena, J.-P.; Grätzel, M.; Hagfeldt, A.; Abate, A. (Angew. Chem., Int. Ed., 2018)

(untitled) - Chen, H.; Xiang, S.; Li, W.; Liu, H.; Zhu, L.; Yang, S. (Sol. RRL, 2018)

(untitled) - Zhang, Q.; Yin, Y. (ACS Cent. Sci., 2018)

(untitled) - Konstantakou, M.; Stergiopoulos, T. (J. Mater. Chem. A, 2017)

(untitled) - Dong, Y.; Zou, Y.; Song, J.; Song, X.; Zeng, H. (J. Mater. Chem. C, 2017)

(untitled) - Swarnkar, A.; Ravi, V. K.; Nag, A. (ACS Energy Lett., 2017)

(untitled) - Sun, J.; Yang, J.; Lee, J. I.; Cho, J. H.; Kang, M. S. (J. Phys. Chem. Lett., 2018)

(untitled) - Yang, G.-L.; Zhong, H.-Z. (Chin. Chem. Lett., 2016)

(untitled) - Bai, S.; Yuan, Z.; Gao, F. (J. Mater. Chem. C, 2016)

(untitled) - Chatterjee, S.; Pal, A. J. (J. Mater. Chem. A, 2018)

(untitled) - Yan, J.; Qiu, W.; Wu, G.; Heremans, P.; Chen, H. (J. Mater. Chem. A, 2018)

(untitled) - Hu, H.; Dong, B.; Zhang, W. (J. Mater. Chem. A, 2017)

(untitled) - Giustino, F.; Snaith, H. J. (ACS Energy Lett., 2016)

(untitled) - Zhang, M.; Lyu, M.; Chen, P.; Hao, M.; Yun, J.-H.; Wang, L. (Asia-Pac. J. Chem. Eng., 2016)

(untitled) - Ganose, A. M.; Savory, C. N.; Scanlon, D. O. (Chem. Commun., 2017)

(untitled) - Liu, C.; Li, W.; Fan, J.; Mai, Y. (J. Energy Chem., 2018)

(untitled) - Liang, L.; Gao, P. (Adv. Sci., 2018)

(untitled) - Pazoki, M.; Edvinsson, T. (Sustainable Energy Fuels, 2018)

(untitled) - Boix, P. P.; Agarwala, S.; Koh, T. M.; Mathews, N.; Mhaisalkar, S. G. (J. Phys. Chem. Lett., 2015)

(untitled) - Kojima, A.; Teshima, K.; Shirai, Y.; Miyasaka, T. (J. Am. Chem. Soc., 2009)

(untitled) - Ogomi, Y.; Morita, A.; Tsukamoto, S.; Saitho, T.; Fujikawa, N.; Shen, Q.; Toyoda, T.; Yoshino, K.; Pandey, S. S.; Ma, T.; Hayase, S. (J. Phys. Chem. Lett., 2014)

(untitled) - Liang, J.; Zhao, P.; Wang, C.; Wang, Y.; Hu, Y.; Zhu, G.; Ma, L.; Liu, J.; Jin, Z. (J. Am. Chem. Soc., 2017)

(untitled) - Yang, Z.; Rajagopal, A.; Jen, A. K.-Y. (Adv. Mater., 2017)

(untitled) - Ke, W.; Stoumpos, C. C.; Spanopoulos, I.; Mao, L.; Chen, M.; Wasielewski, M. R.; Kanatzidis, M. G. (J. Am. Chem. Soc., 2017)

(untitled) - Chen, L.-J.; Lee, C.-R.; Chuang, Y.-J.; Wu, Z.-H.; Chen, C. (J. Phys. Chem. Lett., 2016)

(untitled) - Tsai, C.-M.; Mohanta, N.; Wang, C.-Y.; Lin, Y.-P.; Yang, Y.-W.; Wang, C.-L.; Hung, C.-H.; Diau, E. W.-G. (Angew. Chem., Int. Ed., 2017)

(untitled) - Hao, F.; Stoumpos, C. C.; Cao, D. H.; Chang, R. P. H.; Kanatzidis, M. G. (Nat. Photonics, 2014)

(untitled) - Cao, D. H.; Stoumpos, C. C.; Yokoyama, T.; Logsdon, J. L.; Song, T.-B.; Farha, O. K.; Wasielewski, M. R.; Hupp, J. T.; Kanatzidis, M. G. (ACS Energy Lett., 2017)

(untitled) - Shao, S.; Liu, J.; Portale, G.; Fang, H.-H.; Blake, G. R.; ten Brink, G. H.; Koster, L. J. A.; Loi, M. A. (Adv. Energy Mater., 2018)

(untitled) - Zhu, Z.; Chueh, C.-C.; Li, N.; Mao, C.; Jen, A. K.-Y. (Adv. Mater., 2018)

(untitled) - Jung, M.-C.; Raga, S. R.; Qi, Y. (RSC Adv., 2016)

(untitled) - Bernal, C.; Yang, K. (J. Phys. Chem. C, 2014)

(untitled) - Song, T.-B.; Yokoyama, T.; Aramaki, S.; Kanatzidis, M. G. (ACS Energy Lett., 2017)

(untitled) - Yu, Y.; Zhao, D.; Grice, C. R.; Meng, W.; Wang, C.; Liao, W.; Cimaroli, A. J.; Zhang, H.; Zhu, K.; Yan, Y. (RSC Adv., 2016)

(untitled) - Koh, T. M.; Krishnamoorthy, T.; Yantara, N.; Shi, C.; Leong, W. L.; Boix, P. P.; Grimsdale, A. C.; Mhaisalkar, S. G.; Mathews, N. (J. Mater. Chem. A, 2015)

(untitled) - Jiang, Y.; Zhang, H.; Qiu, X.; Cao, B. (Mater. Lett., 2017)

(untitled) - Zhang, Z.; Li, X.; Xia, X.; Wang, Z.; Huang, Z.; Lei, B.; Gao, Y. (J. Phys. Chem. Lett., 2017)

(untitled) - Lyu, M.; Yun, J.-H.; Cai, M.; Jiao, Y.; Bernhardt, P. V.; Zhang, M.; Wang, Q.; Du, A.; Wang, H.; Liu, G.; Wang, L. (Nano Res., 2016)

(untitled) - Kong, M.; Hu, H.; Wan, L.; Chen, M.; Gan, Y.; Wang, J.; Chen, F.; Dong, B.; Eder, D.; Wang, S. (RSC Adv., 2017)

(untitled) - Nie, R.; Mehta, A.; Park, B.-w.; Kwon, H.-W.; Im, J.; Seok, S. I. (J. Am. Chem. Soc., 2018)

(untitled) - Saparov, B.; Hong, F.; Sun, J.-P.; Duan, H.-S.; Meng, W.; Cameron, S.; Hill, I. G.; Yan, Y.; Mitzi, D. B. (Chem. Mater., 2015)

(untitled) - Singh, A.; Boopathi, K. M.; Mohapatra, A.; Chen, Y. F.; Li, G.; Chu, C. W. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Boopathi, K. M.; Karuppuswamy, P.; Singh, A.; Hanmandlu, C.; Lin, L.; Abbas, S. A.; Chang, C. C.; Wang, P. C.; Li, G.; Chu, C. W. (J. Mater. Chem. A, 2017)

(untitled) - Harikesh, P. C.; Mulmudi, H. K.; Ghosh, B.; Goh, T. W.; Teng, Y. T.; Thirumal, K.; Lockrey, M.; Weber, K.; Koh, T. M.; Li, S.; Mhaisalkar, S.; Mathews, N. (Chem. Mater., 2016)

(untitled) - Stoumpos, C. C.; Malliakas, C. D.; Kanatzidis, M. G. (Inorg. Chem., 2013)

(untitled) - Zong, Y.; Wang, N.; Zhang, L.; Ju, M.-G.; Zeng, X. C.; Sun, X. W.; Zhou, Y.; Padture, N. P. (Angew. Chem., Int. Ed., 2017)

(untitled) - Tsai, C.-M.; Wu, H.-P.; Chang, S.-T.; Huang, C.-F.; Wang, C.-H.; Narra, S.; Yang, Y.-W.; Wang, C.-L.; Hung, C.-H.; Diau, E. W.-G. (ACS Energy Lett., 2016)

(untitled) - Liu, F.; Ding, C.; Zhang, Y.; Ripolles, T. S.; Kamisaka, T.; Toyoda, T.; Hayase, S.; Minemoto, T.; Yoshino, K.; Dai, S.; Yanagida, M.; Noguchi, H.; et al. (J. Am. Chem. Soc., 2017)

(untitled) - Leijtens, T.; Prasanna, R.; Gold-Parker, A.; Toney, M. F.; McGehee, M. D. (ACS Energy Lett., 2017)

(untitled) - Eperon, G. E.; Ginger, D. S. (ACS Energy Lett., 2017)

(untitled) - Liu, C.; Li, W.; Li, H.; Zhang, C.; Fan, J.; Mai, Y. (Nanoscale, 2017)

(untitled) - Arunkumar, P.; Gil, K. H.; Won, S.; Unithrattil, S.; Kim, Y. H.; Kim, H. J.; Im, W. B. (J. Phys. Chem. Lett., 2017)

(untitled) - Liu, H.; Wu, Z.; Shao, J.; Yao, D.; Gao, H.; Liu, Y.; Yu, W.; Zhang, H.; Yang, B. (ACS Nano, 2017)

(untitled) - Singh, P.; Rana, P. J. S.; Dhingra, P.; Kar, P. (J. Mater. Chem. C, 2016)

(untitled) - Lau, C. F. J.; Zhang, M.; Deng, X.; Zheng, J.; Bing, J.; Ma, Q.; Kim, J.; Hu, L.; Green, M. A.; Huang, S.; Ho-Baillie, A. (ACS Energy Lett., 2017)

(untitled) - Lau, C. F. J.; Deng, X.; Zheng, J.; Kim, J.; Zhang, Z.; Zhang, M.; Bing, J.; Wilkinson, B.; Hu, L.; Patterson, R.; Huang, S.; Ho-Baillie, A. (J. Mater. Chem. A, 2018)

(untitled) - Wang, Z.-K.; Li, M.; Yang, Y.-G.; Hu, Y.; Ma, H.; Gao, X.-Y.; Liao, L.-S. (Adv. Mater., 2016)

(untitled) - Zhu, F.; Gentry, N. E.; Men, L.; White, M. A.; Vela, J. (J. Phys. Chem. C, 2018)

(untitled) - Wang, L.-Z.; Zhao, Y.-Q.; Liu, B.; Wu, L.-J.; Cai, M.-Q. (Phys. Chem. Chem. Phys., 2016)

(untitled) - Yao, Z.; Yang, Z.; Liu, Y.; Zhao, W.; Zhang, X.; Liu, B.; Wu, H.; Liu, S. (Frank) (RSC Adv., 2017)

(untitled) - Zhang, M.; Lyu, M.; Yun, J.-H.; Noori, M.; Zhou, X.; Cooling, N. A.; Wang, Q.; Yu, H.; Dastoor, P. C.; Wang, L. (Nano Res., 2016)

(untitled) - Rahul; Singh, P. K.; Singh, R.; Singh, V.; Bhattacharya, B.; Khan, Z. H. (Mater. Res. Bull., 2018)

(untitled) - Moghe, D.; Wang, L.; Traverse, C. J.; Redoute, A.; Sponseller, M.; Brown, P. R.; Bulović, V.; Lunt, R. R. (Nano Energy, 2016)

(untitled) - Noel, N. K.; Stranks, S. D.; Abate, A.; Wehrenfennig, C.; Guarnera, S.; Haghighirad, A.-A.; Sadhanala, A.; Eperon, G. E.; Pathak, S. K.; Johnston, M. B.; Petrozza, A.; Herz, L. M.; et al. (Energy Environ. Sci., 2014)

(untitled) - Qiu, X.; Cao, B.; Yuan, S.; Chen, X.; Qiu, Z.; Jiang, Y.; Ye, Q.; Wang, H.; Zeng, H.; Liu, J.; Kanatzidis, M. G. (Sol. Energy Mater. Sol. Cells, 2017)

(untitled) - Fujihara, T.; Terakawa, S.; Matsushima, T.; Qin, C.; Yahiro, M.; Adachi, C. (J. Mater. Chem. C, 2017)

(untitled) - Hao, F.; Stoumpos, C. C.; Guo, P.; Zhou, N.; Marks, T. J.; Chang, R. P. H.; Kanatzidis, M. G. (J. Am. Chem. Soc., 2015)

(untitled) - Yokoyama, T.; Cao, D. H.; Stoumpos, C. C.; Song, T.-B.; Sato, Y.; Aramaki, S.; Kanatzidis, M. G. (J. Phys. Chem. Lett., 2016)

(untitled) - Lee, Y. M.; Park, J.; Yu, B. D.; Hong, S.; Jung, M.-C.; Nakamura, M. (J. Phys. Chem. Lett., 2018)

(untitled) - Jung, Y.-K.; Lee, J.-H.; Walsh, A.; Soon, A. (Chem. Mater., 2017)

(untitled) - Handa, T.; Yamada, T.; Kubota, H.; Ise, S.; Miyamoto, Y.; Kanemitsu, Y. (J. Phys. Chem. C, 2017)

(untitled) - Song, T.-B.; Yokoyama, T.; Stoumpos, C. C.; Logsdon, J.; Cao, D. H.; Wasielewski, M. R.; Aramaki, S.; Kanatzidis, M. G. (J. Am. Chem. Soc., 2017)

(untitled) - Lee, S. J.; Shin, S. S.; Im, J.; Ahn, T. K.; Noh, J. H.; Jeon, N. J.; Seok, S. I.; Seo, J. (ACS Energy Lett., 2018)

(untitled) - Li, W.; Li, J.; Li, J.; Fan, J.; Mai, Y.; Wang, L. (J. Mater. Chem. A, 2016)

(untitled) - Waleed, A.; Tavakoli, M. M.; Gu, L.; Wang, Z.; Zhang, D.; Manikandan, A.; Zhang, Q.; Zhang, R.; Chueh, Y.-L.; Fan, Z. (Nano Lett., 2017)

(untitled) - Nishikubo, R.; Ishida, N.; Katsuki, Y.; Wakamiya, A.; Saeki, A. (J. Phys. Chem. C, 2017)

(untitled) - Gupta, S.; Cahen, D.; Hodes, G. (J. Phys. Chem. C, 2018)

(untitled) - Ma, L.; Hao, F.; Stoumpos, C. C.; Phelan, B. T.; Wasielewski, M. R.; Kanatzidis, M. G. (J. Am. Chem. Soc., 2016)

(untitled) - Peedikakkandy, L.; Bhargava, P. (RSC Adv., 2016)

(untitled) - Sabba, D.; Mulmudi, H. K.; Prabhakar, R. R.; Krishnamoorthy, T.; Baikie, T.; Boix, P. P.; Mhaisalkar, S.; Mathews, N. (J. Phys. Chem. C, 2015)

(untitled) - Zhu, W.; Xin, G.; Wang, Y.; Min, X.; Yao, T.; Xu, W.; Fang, M.; Shi, S.; Shi, J.; Lian, J. (J. Mater. Chem. A, 2018)

(untitled) - Lee, B.; Krenselewski, A.; Baik, S. I.; Seidman, D. N.; Chang, R. P. H. (Sustainable Energy Fuels, 2017)

(untitled) - Dolzhnikov, D. S.; Wang, C.; Xu, Y.; Kanatzidis, M. G.; Weiss, E. A. (Chem. Mater., 2017)

(untitled) - Jellicoe, T. C.; Richter, J. M.; Glass, H. F. J.; Tabachnyk, M.; Brady, R.; Dutton, S. E.; Rao, A.; Friend, R. H.; Credgington, D.; Greenham, N. C.; Böhm, M. L. (J. Am. Chem. Soc., 2016)

(untitled) - Wong, A. B.; Bekenstein, Y.; Kang, J.; Kley, C. S.; Kim, D.; Gibson, N. A.; Zhang, D.; Yu, Y.; Leone, S. R.; Wang, L.-W.; Alivisatos, A. P.; Yang, P. (Nano Lett., 2018)

(untitled) - Wang, A.; Yan, X.; Zhang, M.; Sun, S.; Yang, M.; Shen, W.; Pan, X.; Wang, P.; Deng, Z. (Chem. Mater., 2016)

(untitled) - Rajendra Kumar, G.; Kim, H.-J.; Karupannan, S.; Prabakar, K. (J. Phys. Chem. C, 2017)

(untitled) - Wang, A.; Guo, Y.; Muhammad, F.; Deng, Z. (Chem. Mater., 2017)

(untitled) - Rakita, Y.; Gupta, S.; Cahen, D.; Hodes, G. (Chem. Mater., 2017)

(untitled) - Hsu, H.-Y.; Ji, L.; Du, M.; Zhao, J.; Yu, E. T.; Bard, A. J. (Electrochim. Acta, 2016)

(untitled) - Ma, S.; Shang, M.; Yu, L.; Dong, L. (J. Mater. Chem. A, 2015)

(untitled) - Sun, P.-P.; Li, Q.-S.; Yang, L.-N.; Li, Z.-S. (Nanoscale, 2016)

(untitled) - Krishnamoorthy, T.; Ding, H.; Yan, C.; Leong, W. L.; Baikie, T.; Zhang, Z.; Sherburne, M.; Li, S.; Asta, M.; Mathews, N.; Mhaisalkar, S. G. (J. Mater. Chem. A, 2015)

(untitled) - Ming, W.; Shi, H.; Du, M.-H. (J. Mater. Chem. A, 2016)

(untitled) - Zhao, Y.-Q.; Liu, B.; Yu, Z.-L.; Cao, D.; Cai, M.-Q. (Electrochim. Acta, 2017)

(untitled) - Cheng, P.; Wu, T.; Zhang, J.; Li, Y.; Liu, J.; Jiang, L.; Mao, X.; Lu, R.-F.; Deng, W.-Q.; Han, K. (J. Phys. Chem. Lett., 2017)

(untitled) - Kopacic, I.; Friesenbichler, B.; Hoefler, S. F.; Kunert, B.; Plank, H.; Rath, T.; Trimmel, G. (ACS Appl. Energy Mater., 2018)

(untitled) - Sun, P.-P.; Chi, W.-J.; Li, Z.-S. (Phys. Chem. Chem. Phys., 2016)

(untitled) - Nagane, S.; Ghosh, D.; Hoye, R. L. Z.; Zhao, B.; Ahmad, S.; Walker, A. B.; Islam, M. S.; Ogale, S.; Sadhanala, A. (J. Phys. Chem. C, 2018)

(untitled) - Zhang, X.; Yin, J.; Nie, Z.; Zhang, Q.; Sui, N.; Chen, B.; Zhang, Y.; Qu, K.; Zhao, J.; Zhou, H. (RSC Adv., 2017)

(untitled) - Nie, Z.; Yin, J.; Zhou, H.; Chai, N.; Chen, B.; Zhang, Y.; Qu, K.; Shen, G.; Ma, H.; Li, Y.; Zhao, J.; Zhang, X. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Xiao, Z.-L.; Chen, H.-Z.; Shi, M.-M.; Wu, G.; Zhou, R.-J.; Yang, Z.-S.; Wang, M.; Tang, B.-Z. (Mater. Sci. Eng., B, 2005)

(untitled) - Li, X.; Zhong, X.; Hu, Y.; Li, B.; Sheng, Y.; Zhang, Y.; Weng, C.; Feng, M.; Han, H.; Wang, J. (J. Phys. Chem. Lett., 2017)

(untitled) - Li, X.; Li, B.; Chang, J.; Ding, B.; Zheng, S.; Wu, Y.; Yang, J.; Yang, G.; Zhong, X.; Wang, J. (ACS Appl. Energy Mater., 2018)

(untitled) - Cortecchia, D.; Dewi, H. A.; Yin, J.; Bruno, A.; Chen, S.; Baikie, T.; Boix, P. P.; Grätzel, M.; Mhaisalkar, S.; Soci, C.; Mathews, N. (Inorg. Chem., 2016)

(untitled) - Hebig, J.-C.; Kühn, I.; Flohre, J.; Kirchartz, T. (ACS Energy Lett., 2016)

(untitled) - Jiang, F.; Yang, D.; Jiang, Y.; Liu, T.; Zhao, X.; Ming, Y.; Luo, B.; Qin, F.; Fan, J.; Han, H.; Zhang, L.; Zhou, Y. (J. Am. Chem. Soc., 2018)

(untitled) - McDonald, C.; Ni, C.; Švrček, V.; Lozac'h, M.; Connor, P. A.; Maguire, P.; Irvine, J. T. S.; Mariotti, D. (Nanoscale, 2017)

(untitled) - Eckhardt, K.; Bon, V.; Getzschmann, J.; Grothe, J.; Wisser, F. M.; Kaskel, S. (Chem. Commun., 2016)

(untitled) - Singh, T.; Kulkarni, A.; Ikegami, M.; Miyasaka, T. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Pious, J. K.; Lekshmi, M. L.; Muthu, C.; Rakhi, R. B.; Nair, V. C. (ACS Omega, 2017)

(untitled) - Zhang, Y.; Yin, J.; Parida, M. R.; Ahmed, G. H.; Pan, J.; Bakr, O. M.; Brédas, J.-L.; Mohammed, O. F. (J. Phys. Chem. Lett., 2017)

(untitled) - Kulkarni, A.; Singh, T.; Ikegami, M.; Miyasaka, T. (RSC Adv., 2017)

(untitled) - Abulikemu, M.; Ould-Chikh, S.; Miao, X.; Alarousu, E.; Murali, B.; Ngongang Ndjawa, G. O.; Barbé, J.; El Labban, A.; Amassian, A.; Del Gobbo, S. (J. Mater. Chem. A, 2016)

(untitled) - Wang, H.; Tian, J.; Jiang, K.; Zhang, Y.; Fan, H.; Huang, J.; Yang, L.-m.; Guan, B.; Song, Y. (RSC Adv., 2017)

(untitled) - Ni, C.; Hedley, G.; Payne, J.; Svrcek, V.; McDonald, C.; Jagadamma, L. K.; Edwards, P.; Martin, R.; Jain, G.; Carolan, D.; Mariotti, D.; Maguire, P.; et al. (Nat. Commun., 2017)

(untitled) - Leng, M.; Yang, Y.; Zeng, K.; Chen, Z.; Tan, Z.; Li, S.; Li, J.; Xu, B.; Li, D.; Hautzinger, M. P.; Fu, Y.; Zhai, T.; et al. (Adv. Funct. Mater., 2018)

(untitled) - Yang, B.; Chen, J.; Hong, F.; Mao, X.; Zheng, K.; Yang, S.; Li, Y.; Pullerits, T.; Deng, W.; Han, K. (Angew. Chem., Int. Ed., 2017)

(untitled) - Wei, F.; Deng, Z.; Sun, S.; Xie, F.; Kieslich, G.; Evans, D. M.; Carpenter, M. A.; Bristowe, P. D.; Cheetham, A. K. (Mater. Horiz., 2016)

(untitled) - Scholz, M.; Flender, O.; Oum, K.; Lenzer, T. (J. Phys. Chem. C, 2017)

(untitled) - Khoram, P.; Brittman, S.; Dzik, W. I.; Reek, J. N. H.; Garnett, E. C. (J. Phys. Chem. C, 2016)

(untitled) - Tong, X.-W.; Kong, W.-Y.; Wang, Y.-Y.; Zhu, J.-M.; Luo, L.-B.; Wang, Z.-H. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Bai, F.; Hu, Y.; Hu, Y.; Qiu, T.; Miao, X.; Zhang, S. (Sol. Energy Mater. Sol. Cells, 2018)

(untitled) - Li, T.; Hu, Y.; Morrison, C. A.; Wu, W.; Han, H.; Robertson, N. (Sustainable Energy Fuels, 2017)

(untitled) - Zhang, W.; Tao, K.; Ji, C.; Sun, Z.; Han, S.; Zhang, J.; Wu, Z.; Luo, J. (Inorg. Chem., 2018)

(untitled) - Adonin, S. A.; Frolova, L. A.; Sokolov, M. N.; Shilov, G. V.; Korchagin, D. V.; Fedin, V. P.; Aldoshin, S. M.; Stevenson, K. J.; Troshin, P. A. (Adv. Energy Mater., 2018)

(untitled) - Ji, C.; Sun, Z.; Zeb, A.; Liu, S.; Zhang, J.; Hong, M.; Luo, J. (J. Phys. Chem. Lett., 2017)

(untitled) - Jain, A.; Voznyy, O.; Sargent, E. H. (J. Phys. Chem. C, 2017)

(untitled) - Pazoki, M.; Röckert, A.; Wolf, M. J.; Imani, R.; Edvinsson, T.; Kullgren, J. (J. Mater. Chem. A, 2017)

(untitled) - Ju, M.-G.; Chen, M.; Zhou, Y.; Garces, H. F.; Dai, J.; Ma, L.; Padture, N. P.; Zeng, X. C. (ACS Energy Lett., 2018)

(untitled) - Li, Y.-J.; Wu, T.; Sun, L.; Yang, R.-X.; Jiang, L.; Cheng, P.-F.; Hao, Q.-Q.; Wang, T.-J.; Lu, R.-F.; Deng, W.-Q. (RSC Adv., 2017)

(untitled) - Zhou, J.; Xia, Z.; Molokeev, M. S.; Zhang, X.; Peng, D.; Liu, Q. (J. Mater. Chem. A, 2017)

(untitled) - McClure, E. T.; Ball, M. R.; Windl, W.; Woodward, P. M. (Chem. Mater., 2016)

(untitled) - Volonakis, G.; Filip, M. R.; Haghighirad, A. A.; Sakai, N.; Wenger, B.; Snaith, H. J.; Giustino, F. (J. Phys. Chem. Lett., 2016)

(untitled) - Filip, M. R.; Hillman, S.; Haghighirad, A. A.; Snaith, H. J.; Giustino, F. (J. Phys. Chem. Lett., 2016)

(untitled) - Yang, J.; Zhang, P.; Wei, S.-H. (J. Phys. Chem. Lett., 2018)

(untitled) - Slavney, A. H.; Hu, T.; Lindenberg, A. M.; Karunadasa, H. I. (J. Am. Chem. Soc., 2016)

(untitled) - Li, Q.; Wang, Y.; Pan, W.; Yang, W.; Zou, B.; Tang, J.; Quan, Z. (Angew. Chem., Int. Ed., 2017)

(untitled) - Greul, E.; Petrus, M. L.; Binek, A.; Docampo, P.; Bein, T. (J. Mater. Chem. A, 2017)

(untitled) - Wei, F.; Deng, Z.; Sun, S.; Zhang, F.; Evans, D. M.; Kieslich, G.; Tominaka, S.; Carpenter, M. A.; Zhang, J.; Bristowe, P. D.; Cheetham, A. K. (Chem. Mater., 2017)

(untitled) - Cheng, P.; Wu, T.; Li, Y.; Jiang, L.; Deng, W.; Han, K. (New J. Chem., 2017)

(untitled) - Debbichi, L.; Lee, S.; Cho, H.; Rappe, A. M.; Hong, K.-H.; Jang, M. S.; Kim, H. (Adv. Mater., 2018)

(untitled) - Zhou, J.; Rong, X.; Molokeev, M. S.; Zhang, X.; Xia, Z. (J. Mater. Chem. A, 2018)

(untitled) - Luo, J.; Li, S.; Wu, H.; Zhou, Y.; Li, Y.; Liu, J.; Li, J.; Li, K.; Yi, F.; Niu, G.; Tang, J. (ACS Photonics, 2018)

(untitled) - Nila Nandha, K.; Nag, A. (Chem. Commun., 2018)

(untitled) - Dai, J.; Ma, L.; Ju, M.; Huang, J.; Zeng, X. C. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Xu, J.; Liu, J.-B.; Liu, B.-X.; Huang, B. (J. Phys. Chem. Lett., 2017)

(untitled) - Lozhkina, O. A.; Murashkina, A. A.; Elizarov, M. S.; Shilovskikh, V. V.; Zolotarev, A. A.; Kapitonov, Y. V.; Kevorkyants, R.; Emeline, A. V.; Miyasaka, T. (Chem. Phys. Lett., 2018)

(untitled) - Savory, C. N.; Walsh, A.; Scanlon, D. O. (ACS Energy Lett., 2016)

(untitled) - Filip, M. R.; Liu, X.; Miglio, A.; Hautier, G.; Giustino, F. (J. Phys. Chem. C, 2018)

(untitled) - Feng, H.-J.; Deng, W.; Yang, K.; Huang, J.; Zeng, X. C. (J. Phys. Chem. C, 2017)

(untitled) - Nakajima, T.; Sawada, K. (J. Phys. Chem. Lett., 2017)

(untitled) - Bartesaghi, D.; Slavney, A. H.; Gélvez-Rueda, M. C.; Connor, B. A.; Grozema, F. C.; Karunadasa, H. I.; Savenije, T. J. (J. Phys. Chem. C, 2018)

(untitled) - Dong, L.; Sun, S.; Deng, Z.; Li, W.; Wei, F.; Qi, Y.; Li, Y.; Li, X.; Lu, P.; Ramamurty, U. (Comput. Mater. Sci., 2018)

(untitled) - Creutz, S. E.; Crites, E. N.; De Siena, M. C.; Gamelin, D. R. (Nano Lett., 2018)

(untitled) - Zhao, X.-G.; Yang, J.-H.; Fu, Y.; Yang, D.; Xu, Q.; Yu, L.; Wei, S.-H.; Zhang, L. (J. Am. Chem. Soc., 2017)

(untitled) - Volonakis, G.; Haghighirad, A. A.; Snaith, H. J.; Giustino, F. (J. Phys. Chem. Lett., 2017)

(untitled) - Giorgi, G.; Yamashita, K. (Chem. Lett., 2015)

(untitled) - Liu, B.; Long, M.; Cai, M.-Q.; Yang, J. (J. Phys. D: Appl. Phys., 2018)

(untitled) - Etgar, L. (Energy Environ. Sci., 2018)

(untitled) - Straus, D. B.; Kagan, C. R. (J. Phys. Chem. Lett., 2018)

(untitled) - Tang, G.; Xiao, Z.; Hosono, H.; Kamiya, T.; Fang, D.; Hong, J. (J. Phys. Chem. Lett., 2018)

(untitled) - Todorov, T.; Gershon, T.; Gunawan, O.; Sturdevant, C.; Guha, S. (Appl. Phys. Lett., 2014)

(untitled) - Etgar, L.; Gao, P.; Qin, P.; Graetzel, M.; Nazeeruddin, M. K. (J. Mater. Chem. A, 2014)

(untitled) - Li, Y.; Zhu, J.; Huang, Y.; Wei, J.; Liu, F.; Shao, Z.; Hu, L.; Chen, S.; Yang, S.; Tang, J.; Yao, J.; Dai, S. (Nanoscale, 2015)

(untitled) - Hu, L.; Yang, Z.; Mandelis, A.; Melnikov, A.; Lan, X.; Walters, G.; Hoogland, S.; Sargent, E. H. (J. Phys. Chem. C, 2016)

(untitled) - Yang, Z.; Janmohamed, A.; Lan, X.; García de Arquer, F. P.; Voznyy, O.; Yassitepe, E.; Kim, G.-H.; Ning, Z.; Gong, X.; Comin, R.; Sargent, E. H. (Nano Lett., 2015)